IS THERE INNOVATION IN THE FAIR? AN ANALYSIS OF CREATION AND MANUFACTURE OF "MODINHA" IN FAIR OF JOSÉ AVELINO STREET (Gestão & Regionalidade, 2019)
The aim of this paper was to identify the process of innovation in modinha manufacture companies in José Avelino Street Fair. To achieve this goal, a case study in José Avelino Street Fair. Data were collected through in-depth interviews with 11 stallholders and analyzed with content analysis. It was found that, although the Fair is recognized as a fashion hub and be able to create fashion, there is a great outside influence, especially novels, being a mass market. It was also found that the predominant innovative strategy is imitative. There is an endless cycle that when there is an innovation, market traders mimic each other, leading to saturation, with no products differentiation and low prices causing a fierce competition between companies, inducing them to seek innovations to excel. Thus, imitation leads to innovation.
Keywords: Innovation; Fashion; Imitation; Modinha; Fair